Tarpenieto na kamaka . The Patience of the Stone - Bonev, Konstantin; Valkanova, Rossitsa (Bulgaria, 1998)
Soros Documentary Fund In a forsaken village somewhere in the eastern part of Rhodopes Mountains, near the Greek border, a bunch of old men and women carry on the remains of their days. Neglected by the state and forgotten by society, and left entirely to themselves, they cling to life with stubborn determination. Filmed on Christmas Eve in the little village, the film features a day in the life of its elderly inhabitants.